2020
DOI: 10.1186/s12889-019-8049-6
|View full text |Cite
|
Sign up to set email alerts
|

Reducing financial barriers through the implementation of voucher incentives to promote children’s participation in community sport in Australia

Abstract: Background: Participation in organised sport and physical activity contributes to health-enhancing levels of leisure time physical activity. In Australia, 58% of children aged 0-14 years participated at least once a week in October 2015-December 2017. To overcome the frequently cited cost barrier, sports voucher incentives have been widely implemented across Australia. Method: The financial value of jurisdictional vouchers and the National median financial value were used to calculate the proportion of total a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 22 publications
2
34
0
2
Order By: Relevance
“…The Active Kids program provided an ‘equal value to all participants, independent of amount spent on the child’s registration’ [ 15 ]. The Active Kids program demonstrated much higher initial population reach to disadvantaged children (38%) than CFTC, likely due to a greater proportion of disadvantaged children’s expenses being supported by the $100 Active Kids voucher [ 12 ]. Differences in program design, stakeholder involvement, and implementation, also contribute to the different reach between programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Active Kids program provided an ‘equal value to all participants, independent of amount spent on the child’s registration’ [ 15 ]. The Active Kids program demonstrated much higher initial population reach to disadvantaged children (38%) than CFTC, likely due to a greater proportion of disadvantaged children’s expenses being supported by the $100 Active Kids voucher [ 12 ]. Differences in program design, stakeholder involvement, and implementation, also contribute to the different reach between programs.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of children’s structured physical activity participation, financial incentive interventions that aim to reduce the cost of structured physical activity participation have gained political interest [ 12 ]. Cost is a major barrier that is stopping children from starting or continuing to participate in structured physical activities [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…. Contudo, inúmeros fatores podem influenciar a experiência dos jovens no esporte (Reece et al, 2020), como o apoio familiar, acesso e continuidade de programas de prática esportiva, formação dos treinadores, qualidade das relações interpessoais estabelecidas no ambiente de treino (Coutinho, Mesquita, & Fonseca A valorização e promoção de treinos pautados no desenvolvimento positivo dos jovens (Holt et al, 2017;, tem sido reconhecido como facilitador para a transferência de habilidades ao longo da vida. No ambiente da prática esportiva os treinadores têm o poder de influenciar a natureza e a qualidade das experiências esportivas, o que reforça a missão de educar, estimular e criar oportunidade para o crescimento e desenvolvimento pessoal dos atletas (Côté, Strachan, & Fraser-Thomas, 2008;Naylor, 2006;Santos, Gould, & Strachan, 2019).…”
unclassified
“…In Australia, several states and territories have introduced voucher schemes to improve physical activity levels for various target populations including youth, women and girls and disadvantaged and remote communities [20]. Whilst uptake of such voucher schemes appears to be substantial, rigorous evaluation of impact on child physical activity is lacking [20]. A recent study (2020) [20] found Australian parents report a median annual expenditure for child physical activities of $447 (IQR $194.2-936).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst uptake of such voucher schemes appears to be substantial, rigorous evaluation of impact on child physical activity is lacking [20]. A recent study (2020) [20] found Australian parents report a median annual expenditure for child physical activities of $447 (IQR $194.2-936). The median voucher value across the five out of eight Australian State and Territories who have implemented a voucher scheme was found to be AU$150 per annum (range AU$50-200 per annum) [20].…”
Section: Introductionmentioning
confidence: 99%